(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical and psychological factors that determine the effectiveness of innovative educational management based on a synergetic approach. In contemporary pedagogical practice, educational management is no longer limited to administrative regulation, formal planning, or control of institutional processes. It increasingly requires flexible coordination, self-organization, openness to innovation, and the harmonization of different educational actors within a single developmental environment. The synergetic approach makes it possible to understand an educational institution as a complex, open, and dynamically developing system in which teachers, students, administrators, parents, social partners, and digital resources interact with each other and create new qualitative results. The article focuses on the role of pedagogical conditions, leadership culture, collaborative communication, professional motivation, psychological readiness for change, reflexive thinking, and emotional stability in the modernization of educational management. Particular attention is paid to the need to develop an innovative managerial environment that supports initiative, creativity, responsibility, and collective decision-making. The study emphasizes that the effectiveness of management in education depends not only on organizational mechanisms, but also on the psychological climate, the level of trust, the readiness of participants for cooperation, and their ability to adapt to changing educational demands.